2011
DOI: 10.1634/theoncologist.2011-0185
|View full text |Cite
|
Sign up to set email alerts
|

An Emerging Entity: Pancreatic Adenocarcinoma Associated with a Known BRCA Mutation: Clinical Descriptors, Treatment Implications, and Future Directions

Abstract: Learning Objectives After completing this course, the reader will be able to: Describe the genetic syndromes associated with pancreas adenocarcinoma. Explain the potential role of platinum‐based therapy and PARP inhibitors in BRCA‐mutated pancreas adenocarcinoma. This article is available for continuing medical education credit at http://CME.TheOncologist.com Background. BRCA1 and BRCA2 germline mutations are associated with an elevated risk for pancreas adenocarcinoma (PAC). Other BRCA‐associated cancers ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(161 citation statements)
references
References 13 publications
3
155
0
3
Order By: Relevance
“…A similar and parallel picture with pancreatic adenocarcinoma is emerging (19,20), BRCA-related pancreatic adenocarcinoma might exhibit unique biology and natural history. In fact, it might represent components of a subset of pancreatic adenocarcinoma defined by underlying molecular biology in defective homologous recombination mechanism, as seen in other disease types.…”
Section: Min Yuen Teo 1 Eileen M O'reillymentioning
confidence: 86%
See 2 more Smart Citations
“…A similar and parallel picture with pancreatic adenocarcinoma is emerging (19,20), BRCA-related pancreatic adenocarcinoma might exhibit unique biology and natural history. In fact, it might represent components of a subset of pancreatic adenocarcinoma defined by underlying molecular biology in defective homologous recombination mechanism, as seen in other disease types.…”
Section: Min Yuen Teo 1 Eileen M O'reillymentioning
confidence: 86%
“…The link between prostate cancer and BRCA1/2 mutations has been established (19,20) and worse clinical outcomes have been suggested (21)(22)(23). Not unlike observations in ovarian and breast cancers, a recent phase II study has shown that these prostate cancers demonstrated heightened response to PARP inhibition (23).…”
Section: Min Yuen Teo 1 Eileen M O'reillymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FrenchCanadian founder mutations in the BRCA1, BRCA2, and PALB2 genes have already been described [11][12][13] , providing the qpcs with a unique opportunity to study the prevalence of those founder mutations among French-Canadian participants with pdac. BRCA1-and BRCA2-associated pdac is of particular interest because those tumours can have beneficial treatment responses to dna cross-linking agents (that is, platinum salts) and parp inhibitors [41][42][43][44][45][46] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several dramatic clinical responses to mitomycin C and to inhibitors of poly (ADPribose) polymerase (PARP) have been reported in pancreatic cancer patients with cancers that harbor inactivating mutations in a Fanconi anemia gene. 39,40 Similarly, germline mutations in the ATM gene predispose to pancreatic cancer, and the ataxia telangiectasia-mutated (ATM) pathway is also potentially therapeutically targetable with existing agents. 24,25 PARP inhibitors, external beam radiation therapy and DNA-PKcs (protein kinase DNA-activated catalytic polypeptide) inhibitors may all be selectively effective in these patients.…”
Section: Applying Advances To Tumor Treatmentmentioning
confidence: 99%